Future of Seizure Prediction and Intervention: Closing the Loop. Issue 3 (June 2015) - Nagaraj, Vivek; Lee, Steven T.; Krook-Magnuson, Esther; Soltesz, Ivan; Benquet, Pascal; Irazoqui, Pedro P.; Netoff, Theoden I.
Abstract : Summary: The ultimate goal of epilepsy therapies is to provide seizure control for all patients while eliminating side effects. Improved specificity of intervention through on-demand approaches may overcome many of the limitations of current intervention strategies. This article reviews the progress in seizure prediction and detection, potential new therapies to provide improved specificity, and devices to achieve these ends. Specifically, we discuss (1) potential signal modalities and algorithms for seizure detection and prediction, (2) closed-loop intervention approaches, and (3) hardware for implementing these algorithms and interventions. Seizure prediction and therapies maximize efficacy, whereas minimizing side effects through improved specificity may represent the future of epilepsy treatments.